CLINICAL AND ECONOMIC ANALYSIS OF THE LONG-TERM MAINTENANCE THERAPY BY COMBINED DRUGS OF BRONCHIAL ASTHMA IN SCHOOL CHILDREN, RESIDENTS OF THE RURAL REGIONS - I.N. Ermakova; S.M. Kushnir; Yu.L. Mizernitsky (Педиатрическая фармакология, 2011)
The purpose of the study: selection of the supporting anti-asthma therapy (SAAT) of the moderate asthma in school children, residents of the village with the lowest ratio of price and efficiency. The maximum frequency of achieving control of asthma was 64%. The spectrum of asthma medicines (drugs) used in outpatient phase is represented. For 7 years, the proportion of the inhaled corticosteroid (ICS) therapy in children with asthma has increased moderately by 5.5 times and was 66%, of which 2/3 was the combination of inhaled glucocorticosteroids. When using the combined drug salmeterol/fluticasone propionate (50/100 mkg) during 3 months, after that fluticasone proionat during next 3 months as a level-controlled asthma the SAAT controlling BA increased 2 times. The cost of drugs accounted for 86% of direct medical costs (DMC), the cost of hospitalization decreased from 80 to 56% (DMC savings — 24%). The results of the analysis of «cost–effectiveness» SAAT allow to review the financial resources for health in favor of providing children with mild asthma inhaled high-performance combination that will improve the quality of medical care for children, residents of the rural regions.Key words: asthma, children, inhaled glucocorticosteriods, combined therapies, pharmacoeconomic analysis.